Repurposing Ketamine in Depression and Related Disorders: Can This Enigmatic Drug Achieve Success? - Carboni, Ezio; Carta, Anna R.; Carboni, Elena; Novelli, Antonello (Frontiers in Neuroscience, 2021)
Repurposing ketamine in the therapy of depression could well represent a breakthrough in understanding the aetiology of depression. Ketamine was originally used as an anaesthetic drug and later its use was extended to other therapeutic applications such as analgesia and the treatment of addiction. At the same time, the abuse of ketamine as a recreational drug has generated a concern for its psychotropic and potential long-term effects; nevertheless, its use as a fast acting antidepressant in treatment-resistant patients has boosted the interest in the mechanism of action both in psychiatry and in the wider area of neuroscience. This article provides a comprehensive overview of the actions of ketamine and intends to cover: i) the evaluation of its clinical use in the treatment of depression and suicidal behaviour; ii) the potential use of ketamine in paediatrics; iii) a description of its mechanism of action; iv) the involvement of specific brain areas in producing antidepressant effects; v) the potential interaction of ketamine with the hypothalamic-pituitary-adrenal axis; vi) the effect of ketamine on neuronal transmission in the bed nucleus of stria terminalis and on its output; vii) the evaluation of any gender-dependent effects of ketamine; viii) the interaction of ketamine with the inflammatory processes involved in depression; ix) the evaluation of the effects observed with single or repeated administration; x) a description of any adverse or cognitive effects and its abuse potential. Finally, this review attempts to assess whether ketamine’s use in depression can improve our knowledge of the etiopathology of depression and whether its therapeutic effect can be considered an actual cure for depression rather than a therapy merely aimed to control the symptoms of depression.